2018
DOI: 10.1080/15374416.2018.1443456
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Connectedness on Depression and Suicidal Ideation Among Bully Victimized Youth

Abstract: This longitudinal study examined the relationship between connectedness subtypes (family, school, community) and youth depression and suicidal ideation across a 6-month period within a sample of bully victimized youth. Participants were 142 youth (74.6% female, 47.18% African American, 36.62% Caucasian), 12-15 years of age (M = 13.6, SD = 1.12), recruited from an emergency department, who screened positive for elevated levels of bullying victimization and were reevaluated at a 6-month follow-up assessment. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 73 publications
4
29
1
1
Order By: Relevance
“…Research on adolescent development indicates that the frequency and intensity of parent-child conflict peaks around middle adolescence and is often driven by the process autonomy development (Smetana, Campione-Barr, & Metzger, 2006). While this finding is novel (specifically as it relates to family communication and perceived burdensomeness), it aligns with prior research that has identified family conflict and communication difficulties with family members as risk factors for suicide in adolescence (Arango et al, 2018;Connor & Reuter, 2006;Halstead, Pavkov, Hecker, & Seliner, 2014).…”
Section: Discussionsupporting
confidence: 64%
“…Research on adolescent development indicates that the frequency and intensity of parent-child conflict peaks around middle adolescence and is often driven by the process autonomy development (Smetana, Campione-Barr, & Metzger, 2006). While this finding is novel (specifically as it relates to family communication and perceived burdensomeness), it aligns with prior research that has identified family conflict and communication difficulties with family members as risk factors for suicide in adolescence (Arango et al, 2018;Connor & Reuter, 2006;Halstead, Pavkov, Hecker, & Seliner, 2014).…”
Section: Discussionsupporting
confidence: 64%
“…Increasing social support, particularly in the domain of the family, is often a key focus of interventions for adolescents at risk for suicide, including our MI‐enhanced safety planning intervention pilot (Czyz, King, & Biermann, ). However, to inform tailored interventions for adolescents at suicide risk and identify the most promising mechanisms of change, it would be informative to consider if different forms of connectedness (e.g., family, peers, school)—previously found to have distinct relationship with suicidal thoughts and behavior among teens (Arango et al., ; Czyz, Liu, & King, ; Kaminski et al., )—may be differentially associated with near‐term risk.…”
Section: Discussionmentioning
confidence: 99%
“…Using Joiner's (2005) interpersonal theory of suicide, after experiencing traditional victimisation, adolescents may be frustrated when their desire to connect with others is not fulfilled. Loneliness and social isolation may ensue (i.e., thwarted belongingness) which, in turn, would heighten the risk of suicidal ideation (see Arango et al, 2018;Hong et al, 2015;McKinnon et al, 2016).…”
Section: Article In Pressmentioning
confidence: 99%